76 Comprehensive Assessment of Rare Genetic Variation in Dilated Cardiomyopathy Genes in Patients and Controls. (6th June 2015) - Tayal, Upasana; Mazzarotto, Francesco; Buchan, Rachel; Walsh, Roddy; Barton, Paul; Ware, James; Cook, Stuart
Abstract : Introduction: Dilated cardiomyopathy (DCM) is a genetically heterogenous condition with mutations reported in at least 50 associated genes. 1 Our consortium has demonstrated the presence of truncating mutations in the giant sarcomeric gene titin (TTN) in up to 27% of DCM 2 making this the commonest genetic cause of DCM. Here we conducted a comprehensive analysis of the frequency of rare coding variants in cardiomyopathy genes in DCM patients and ethnically-matched healthy controls. Methods: We sequenced 64 cardiomyopathy genes in 651 individuals, comprising 234 patients referred for prospective evaluation of DCM with cardiac MRI (54 ± 14 yrs at scan, 70.5% males), 98 end-stage DCM (39 ± 16 yrs on date of transplant/left-ventricular assist device implantation, 83.7% males), and 319 prospectively recruited adult healthy volunteers (HVOL, 42 ± 14 yrs at scan, 46.1% males), who underwent detailed phenotyping with cardiac MRI. Next-generation targeted exon sequencing was performed on the SOLiD 5500xl platform. Variant calling was performed using Lifescope v2.5.1. Data were mapped to the Hg19 (GRCh37) human genome reference. Caucasian ethnicity was confirmed using Principal Component Analysis. Burden testing for potentially disease-causing variation was performed on each gene. Results: DCM patients were enriched for novel protein-altering variants in 28 genes (Table 1 : top 7 genes), but only 5 achieved nominal significance. Truncating variants in TTN (TTNtv) remained significant after multiple testing correction (12% DCM, 1.9% controls, p = 8.1 × 10–6). Rare variation in SCN5A and MYH6, previously reported to play a key role in DCM, were not enriched in DCM (SCN5A – 2.1% DCM, 2.8% controls, p = 0.80; MYH6 –0.9% DCM, 2.2% controls, p = 0.95) and nor were non-synonymous SNPs in TTN (TTNns, 25.6% DCM, 25.7% controls, p = 0.55). Importantly, an additive effect of variation in multiple DCM genes on DCM risk was identified using logistic regression models (p = 5.7 × 10 x -4), demonstrating a multi-genic basis for DCM in some cases. Conclusions: To the best of our knowledge, this is the first comprehensive study of the genetic architecture of DCM compared to an ethnically-matched healthy control cohort. The majority of genes reported to contain rare variants in DCM have similar burdens of variation in controls. Some variants may contribute to disease, but excluding TTNtv the majority of such variants are uninterpretable in the absence of functional or segregation data. References: Mestroni L, Taylor MR. Genetics and genetic testing of dilated cardiomyopathy: a new perspective. Discov Med. 2013;15(80):43-9 Herman DS, Lam L, Taylor MR, Wang L, Teekakirikul P, Christodoulou D, et al . Truncations of titin causing dilated cardiomyopathy. N Engl J Med. 2012;366(7):619-28